Atmospheric Pressure Selective Epitaxial Growth of Heavily in-situ Phosphorous-Doped Si(:C) Raised Sources and Drains. (18th August 2016) - Hartmann, Jean-Michel; Aubin, Joris; Barraud, Sylvain; Samson, Marie-Pierre
Abstract : We have developed an innovative atmospheric pressure process for the selective co-flow deposition of Si(C):P Raised Sources and Drains (RSDs) at 700 °C – 800 °C. A Si:P growth rate that increased as the PH3 mass-flow increased, together a P + ions concentration that reached at most 7x10 19 cm -3, were associated with Si:P layers grown with SiH2 Cl2, HCl and a PH3 1% in H2 bottle (with no dependence whatsoever on growth temperature). Wanting to probe even higher phosphine flows, we have switched over to PH3 5% in H2 bottles and studied at 700°C the growth kinetics and n-type doping of Si. The Si:P growth rate increased, stabilized then decreased (which is most likely due to surface poisoning) as the PH3 mass-flow increased. This was associated with a sharp increase then a stabilization at nearly 10 20 cm -3 of the P + ion concentration. The resulting Si:P layers were single crystalline and slightly rough. Full selectivity versus SiO2 (isolation) and SiN sidewall spacers was achieved on patterned wafers with this heavily chlorinated chemistry. Finally, we have evaluated the feasibility of adding SiCH6 to the gaseous mixture to obtain SiC:P layers. The substitutional C concentration was rather small (at most 0.55%). Meanwhile, the resistivity was at first stable then increased, while the SiC:P growth rate monotonously decreased as the SiCH6 mass-flow went up.